In reply (15.05.2020) - Baum, Philip; Wiegering, Armin (Deutsches Ärzteblatt, 2020)
As Prof Mrozckowski correctly explains, DRG and OPS (Operationen- und Prozedurenschlüssel) codes are generally intended for billing for service rendered. They may bias the results of evaluations and are potentially inferior to data from clinical...